ANALYSIS OF PARKING MANAGEMENT POLICY IN GARUT REGENCY - Ikeu Kania (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
Parking is an inseparable component or aspect of the need for a transportation system because every trip with a private vehicle generally always starts and ends in the parking lot. Regarding parking management in this study, namely analyzing how the Garut Regency Transportation Service carries out parking management in Garut Regency in its implementation, the inhibiting factors that affect parking management, and how the efforts are made to overcome the parking management problem in the Regency arrowroot. The method used by the researcher is a qualitative descriptive method that describes parking management with data collection techniques that include observation, interviews and documentation. The results of this study in parking management are analyzed with management functions, namely planning, organizing, mobilizing and monitoring where there are still many things that need to be improved again because there are so many obstacles and problems in conducting the parking management analysis, which is caused by factors that hinder into the parking lot. Parking management is factors of awareness, communication and coordination, and resource factors carried out by employees and parking attendants involved in managing the parking lot.